The Effects of Life Stress on Men’s Alcohol Use: a Reassessment of Data from the 2012 China Family Panel Studies - Jiafeng Gu; Xing Ming (International Journal of Mental Health and Addiction, 2022)
Drinking alcohol is cited as a way for men to cope with stress, with most of the research emanating from western countries. However, in the East, limited scientific research has been conducted on the relationship between stress and alcohol consumption. Thus, this study aimed to explore the influence of life stress on alcohol use among Chinese men.Our data were drawn from the 2012 China Family Panel Studies that comprised representative samples of the Chinese population. In total, 15,373 Chinese men participated in this study, and their weekly alcohol intake and life stress were evaluated using computer assisted personal interviews. It was found that the greater the overall life pressure experienced by the Chinese men, the less likely they were to engage in both general (OR = 0.977) and heavy drinking (OR = 0.975). Although severe life stress that interfered with daily life did not affect general drinking, it had a negative effect on heavy drinking. As for less severe life stresses, feeling down and sad had an inhibitory effect on male general and heavy drinking, and experiencing loneliness had a similar effect on general drinking but no effect on heavy drinking. Further, perceiving unfriendliness from others had no influence on male drinking behavior. Although feeling disliked by others had no effect on male drinking behavior, it had a significant, positive effect on male heavy drinking. This study found that in China, stress did not increase male alcohol consumption, but rather, inhibited it. Alcohol consumption is not a preferred strategy for Chinese men dealing with stress.